2012
DOI: 10.1302/2046-3758.18.2000083
|View full text |Cite
|
Sign up to set email alerts
|

The modified tibial tubercle osteotomy for anterior knee pain due to chondromalacia patellae in adults

Abstract: ObjectivesTo assess the effectiveness of a modified tibial tubercle osteotomy as a treatment for arthroscopically diagnosed chondromalacia patellae.MethodsA total of 47 consecutive patients (51 knees) with arthroscopically proven chondromalacia, who had failed conservative management, underwent a modified Fulkerson tibial tubercle osteotomy. The mean age was 34.4 years (19.6 to 52.2). Pre-operatively, none of the patients exhibited signs of patellar maltracking or instability in association with their anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Nevertheless those procedures are not correcting the underlying pathomorphology. In respect to a modified version of the Fulkerson osteotomy, Jack et al, in a 5 year follow-up of patients with chronic AKP, found that the Kujala score went from 39.2 to 57.7 and with a success rate of 72% [38] . Patients with lowest Kujala score and younger patients benefitted the most.…”
Section: Limitation and Alternative Proceduresmentioning
confidence: 99%
“…Nevertheless those procedures are not correcting the underlying pathomorphology. In respect to a modified version of the Fulkerson osteotomy, Jack et al, in a 5 year follow-up of patients with chronic AKP, found that the Kujala score went from 39.2 to 57.7 and with a success rate of 72% [38] . Patients with lowest Kujala score and younger patients benefitted the most.…”
Section: Limitation and Alternative Proceduresmentioning
confidence: 99%
“…Fulkerson 23 noted in his series that 1 out of 51 cases sustained a late fracture through the screw site in the tuberosity shingle and was successfully treated with reoperation and bone grafting of the fracture site. Jack et al 31 reported in their study that a patient sustained a nondisplaced fracture through the proximal screw hole after falling. This was successfully treated nonoperatively.…”
Section: Mpfl Reconstructionmentioning
confidence: 99%
“…Wound complications including skin necrosis have been reported after the Maquet procedure 38,39 but have not been commonly reported after anteromedializing osteotomies. Jack et al 31 reported in a study of 51 knees that only 1 patient had a superficial infection that was treated with antibiotics and resolved within 2 weeks. Arthrofibrosis had also been reported in early studies after TTO 23 ; however, recent larger series have not reported this as a complication after this procedure.…”
Section: Mpfl Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical treatment of AKP is not discussed in the literature with the same quality of studies as has been demonstrated for the conservative treatments [4][5][6]. Generally there are few randomised controlled trials (RCTs), and those that have been conducted have failed to prove that surgical therapy is more effective than nonsurgical treatments [7].…”
Section: Introductionmentioning
confidence: 99%